THE ALGORITHMIC MODEL OF LABORATORY DIAGNOSTICS OPTIMIZATION - G. I. Nazarenko; O. V. Andropova (Рациональная фармакотерапия в кардиологии)
The problem of improvement of modern diagnostic technologies is discussed. Introduction of algorithmic approach is able to optimize diagnostics and its costs. Various algorithmic models, their features and structure are reviewed. As an example the algorithm of differential diagnostics of hypokaliemia is presented.